Harry Potter and the Half-Blood Prince Voldemort’s Personality Change as Influenced by His Past Life and Psyche - Perdana, Abhirama S. D. (English Education Department, Universitas Islam Indonesia, 2007)
This study discusses the personality change influenced by the past life in the antagonist character in J.K Rowling’s “Harry Potter and the Half-Blood Prince The Past Experience has an effect in the antagonist character, Lord Voldemort. It is always interesting to discuss the effect of the past experience which can make a difference to someone’s character. Every Person has its own personality but the effect of the past life can make big impact to his/her personality.This study is aimed to analyze what kind of past life which affect the personality of the character, Lord Voldemort. The psychological theory will be used to give explanation about personality and changes of personalities. Furthermore, psychological approach will be used in this study because personality is one of the aspects of a person’s psychology.